SAT0531 COLLAGEN IMAGING USING DUAL-ENERGY COMPUTED TOMOGRAPHY CAN DETECT SOFT-TISSUE INVOLVEMENT OF THE INTERVERTEBRAL DISC IN PATIENTS WITH AXIAL SPONDYLOARTHRITIS. (June 2019) - Diekhoff, Torsten; Hermann, Kay-Geert; Proft, Fabian; Protopopov, Mikhail; Makowski, Marcus R.; Poddubnyy, Denis; ,
Abstract : Background: Based on the unique physical properties of collagen, dual-energy computed tomography (DECT) is able to detect pathological changes in fibrous structures. This has been demonstrated for the Achilles tendon (1) and traumatic disc injury in elderly patients (2). Objectives: The purpose of this study was to assess the diagnostic potential of DECT collagen imaging for the detection of intervertebral disc involvement in patients with axial spondyloarthritis (axSpA) in correlation with osseous lesions in MRI. Methods: Sixteen patients with suspicion of or known axSpA and back pain were included. All patients underwent a 1.5-Tesla-MRI including T1 and STIR sequences and an ultra-low-dose DECT of the spine using two sequential helical acquisitions. DECT images were reconstructed in 120 kV-equivalent standard CT images and collagen maps with 1.0 mm slice thickness in sagittal reconstructions. MRI and CT images (D1 to S1) were scored for transdiscal ankylosis, Andersson lesions, syndesmophytes, spondylitis anterior and fatty corner lesions (when applicable) as well as for degenerative findings. DECT images were scored for a loss of collagen density affecting the nucleus pulposus or the anulus fibrosus. Sensitivity (SE) and specificity (SP) values were calculated. All analyses were performed on the level of the disco vertebral units. Results: Twelve male and four female patients with a mean age of 46.6 ± 11.6 years were included. Eleven were finally diagnosed with axSpA, 3 with degenerative spine disease and 2 with diffuse idiopathic skeletal hyperostosis (DISH). MRI detected 73 lesions in 274 discovertebral units (61 SpA related, 12 degenerative; 26 affecting the disc and 35 affecting the vertebral corner) and CT 68, whereas DECT identified pathologically decreased collagen content in 60 discs (35 in the nucleus and 25 in the anulus). DECT showed high diagnostic accuracy when compared to SpA-related and degenerative changes (MRI and CT combined; SE: 67%; SP 99.5%) and for SpA-lesions only (SE 72%; SP 94.2%), however, was less susceptible for degeneration (SE 60%; SP 81.9%). When comparing disc lesions in SpA as detected by MRI (transdiscal ankylosis and Andersson lesions) with nucleus-pulposus changes in DECT, it showed an SE of 88.5% and an SP of 95.1%. However, the diagnostic accuracy was inferior when comparing anterior spondylitis and fatty corner lesions in MRI with anulus fibrosus changes in DECT (SE 51.4% and SP 97%), although the SE was markedly higher for active inflammatory corner lesion (92.3%) than for fatty marrow lesions (23.3%). The mean radiation exposure was 8.1 ± 3.4 mSv. Conclusion: DECT is able to demonstrate soft-tissue involvement of the disc, especially for transdiscal ankylosis, Andersson lesions and active anterior spondylitis. This can be achieved with considerably low radiation exposure. While measuring the collagen density, it provides additional information to conventional CT and MR images. Thus, it has high potential to develop into a useful tool to further enhance our understanding of pathologic soft-tissue changes in axSpA patients outside the bone and bone marrow. References: [1] Mallinson PI, Stevens C, Reisinger C, Nicolaou S, Munk PL, Ouellette H. Achilles tendinopathy and partial tear diagnosis using dual-energy computed tomography collagen material decomposition application. J Comput Assist Tomogr. [2] Pumberger M, Fuchs M, Engelhard N, et al. Disk injury in patients with vertebral fractures-a prospective diagnostic accuracy study using dual-energy computed tomography. Eur Radiol. 2019. Disclosure of Interests: Torsten Diekhoff Paid instructor for: MSD, AbbVie, Novartis, Canon, but less than 10.000€, Kay-Geert Hermann Paid instructor for: MSD, AbbVie, Novartis, but less than 10.000€, Fabian Proft Grant/research support from: Novartis, Consultant for: yes but less than 10.000, Paid instructor for: yes but less than 10.000, Speakers bureau: yes but less than 10.000, Mikhail Protopopov: None declared, Marcus R Makowski: None declared, Denis Poddubnyy Grant/research support from: AbbVie, Merck Sharp & Dohme, Novartis, Consultant for: AbbVie, Bristol-Myers Squibb, Janssen, Merck Sharp & Dohme, Novartis, Pfizer, UCB Pharma, Speakers bureau: AbbVie, Bristol-Myers Squibb, Janssen, Merck Sharp & Dohme, Novartis, Pfizer, Roche, UCB Pharma